Impact of a training intervention on upper gastrointestinal endoscopy quality over time: Multicenter comparative cohort study - Koggel, Lieke Maria; van Berlo, Jole P.E.; Indemans, Fleur A.; Schrauwen, Ruud W.M.; Lantinga, Marten A.; Siersema, Peter D. (Endoscopy International Open, 2025)
The European Society of Gastrointestinal Endoscopy (ESGE) and British Society of Gastroenterology (BSG) formulated performance measures to improve the detection rate for upper gastrointestinal (UGI) endoscopy. We aimed to assess adherence to and impact of training on adherence to performance measures for UGI endoscopy.In this multicenter, prospective, cohort study, endoscopists at three centers underwent 1-hour face-to-face training based on ESGE and BSG procedure performance measures (≥ 7-minute inspection time; photodocumentation of ≥ 10 anatomical landmarks + abnormalities; standardized terminology; biopsy protocols). A self-developed quality assessment score was used to assess diagnostic UGI endoscopies before (control group) and after (intervention group) training. The primary endpoint was improvement in overall quality score (percentage of the maximum score).Of 1,733 consecutive UGI endoscopies, 570 were eligible for inclusion (mean patient age 60 years [standard deviation 15]; male 47%): 285 in the control group and 285 in the intervention group. Overall quality score increased from 60% before to 67% after the training intervention (difference 7%, 95% confidence interval [CI] 5–10, P < 0.001). Male patients (3.2%, 95% CI 0.7–5.7), alarming features (-3.1%, 95% CI -5.6 to -0.5), and endoscopist age (-0.4% increment per year, 95% CI -0.8 to -0.1) were associated with higher quality scores.Adherence to the ESGE and BSG procedure performance measures for UGI endoscopy persistently increased after a 1-hour face-to-face training intervention, suggesting that a simple training intervention tool can improve the quality of UGI endoscopy and potentially could prevent missed lesions.
Keywords: Endoscopy Upper GI Tract; Quality and logistical aspects; Training; Quality management; Performance and complications; Image and data processing, documentatiton